The Effects of Mergers and Acquisitions on Company Performance - Ching, Jin Wei (2013)
The aim of this dissertation is to identify the effects of mergers and acquisitions on company performance. Throughout the dissertation, the history and definition of M&As are briefly addressed. Then, based on the existing studies and researches, the accounting study approach is chosen to examine on the UK companies. 100 mergers and 100 non-mergers are selected randomly in order to carry out the pre- & post-mergers analysis, as well as mergers & non-mergers analysis.